2023
DOI: 10.1007/s10792-023-02664-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative primary partial occlusion of the PreserFlo MicroShunt to prevent initial postoperative hypotony

Abstract: Purpose The aim of the underlying study was to present a new surgical method in PreserFlo MicroShunt surgery for glaucoma. A removable polyamide suture was placed into the lumen of the MicroShunt during implantation to prevent early postoperative hypotony. Methods Thirty-one patients undergoing stand-alone glaucoma surgery with implantation of a PreserFlo MicroShunt and an intraluminal occlusion were retrospectively reviewed and compared to a control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Reduced flow rates could also lead to decreased tube resistance and subsequent hypotony. Previous measures, such as placing removable polyamide sutures inside the PRESERFLO lumen, have effectively reduced the incidence of post-surgical hypotony [16]. The mechanisms underlying hypotony through reduced inflow and an increase in tube resistance by narrowing the lumen are well-explained by the equations discussed in this study.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Reduced flow rates could also lead to decreased tube resistance and subsequent hypotony. Previous measures, such as placing removable polyamide sutures inside the PRESERFLO lumen, have effectively reduced the incidence of post-surgical hypotony [16]. The mechanisms underlying hypotony through reduced inflow and an increase in tube resistance by narrowing the lumen are well-explained by the equations discussed in this study.…”
Section: Discussionmentioning
confidence: 69%
“…The pressure at the proximal end (P 1 ) should represent the IOP of a human eye implanted with a PRESERFLO device. Unlike our experimental setup, when the PRESERFLO device is implanted in a human patient's eye, the distal end of the PRESERFLO is not free [16,17], and the resistance attributed to Tenon/subconjunctival tissues comes into play. Consequently, after surgical implantation of the PRESERFLO device, the IOP is expected to be higher than the peak pressure observed in the sclera 30 • condition in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…156 Durr et al 157 looked at the success rate of PRE-SERFLO in eyes that had previously undergone a subconjunctival filtering surgery; they reported a complete success rate of 61% after 12 months, which was similarly observed by Schlenker et al 158 Hypotony was found in 63% during the early postoperative period, 159 with 11% having choroidal detachments. The intraoperative primary partial shunt occlusion with an 8.0 polyamide suture was described by Lüke et al 160 and may prevent postoperative hypotony. Despite PRESERFLO's meticulous design to esnsure safety, Saeed et al 161 showed that transient postoperative complications (hypotony, bleb fibrosis, hyphema, keratitis, and choroidal effusion) could be as much as 47%.…”
Section: Efficacy and Safetymentioning
confidence: 99%